Updates on Lisfranc Complex Injuries. Issue 1 (25th January 2021) - Yan, Alan; Chen, Stephen R.; Ma, Xin; Shi, Zhongmin; Hogan, MaCalus
Lisfranc injuries are a disruption of one or more of the tarsometatarsal joints and have an estimated incidence of 1/55 000 people. However, the total number of Lisfranc injuries could be underreported, because almost 20% of these injuries are initially missed. Because of the relative infrequency of these injuries, the current literature is inconsistent in regard to proper treatment. This article provides a review of Lisfranc complex injuries including relevant anatomy, diagnosis, treatment, classifications, operative approaches, and outcomes and complications. Based on existing evidence, it also proposes an algorithm the authors prefer for the evaluation and treatment of Lisfranc complex injuries.